Advances in the development of biomarkers for epilepsy - Pitkänen, Asla; Löscher, Wolfgang; Vezzani, Annamaria; Becker, Albert J; Simonato, Michele; Lukasiuk, Katarzyna; Gröhn, Olli; Bankstahl, Jens P; Friedman, Alon; Aronica, Eleonora; Gorter, Jan A; Ravizza, Teresa; et al. (Lancet neurology, 2016)
Over 50 million people worldwide have epilepsy. In nearly 30% of these cases, epilepsy remains unsatisfactorily controlled despite the availability of over 20 antiepileptic drugs. Moreover, no treatments exist to prevent the development of epilepsy in those at risk, despite an increasing understanding of the underlying molecular and cellular pathways. One of the major factors that have impeded rapid progress in these areas is the complex and multifactorial nature of epilepsy, and its heterogeneity. Therefore, the vision of developing targeted treatments for epilepsy relies upon the development of biomarkers that allow individually tailored treatment. Biomarkers for epilepsy typically fall into two broad categories: diagnostic biomarkers, which provide information on the clinical status of, and potentially the sensitivity to, specific treatments, and prognostic biomarkers, which allow prediction of future clinical features, such as the speed of progression, severity of epilepsy, development of comorbidities, or prediction of remission or cure. Prognostic biomarkers are of particular importance because they could be used to identify which patients will develop epilepsy and which might benefit from preventive treatments. Biomarker research faces several challenges; however, biomarkers could substantially improve the management of people with epilepsy and could lead to prevention in the right person at the right time, rather than just symptomatic treatment.